Students' Critical Thinking Process in Solving Jumping Task According to Gregorc's Thinking Style - Hobri Hobri; Samsul Arifin; Randi Pratama Murtikusuma; Ervin Oktavianingtyas; Inge Wiliandani Setya Putri (Universitas Syiah Kuala, 2021)
Indonesian students are lacking in critical thinking skills, however, studies analyzing critical thinking processes and their relation to thinking styles are limited. This study aimed to describe students critical thinking processes in solving jumping task problems according to Gregorc's thinking style. The subjects of this present qualitative research were eight Year 7 students. The instruments included a thinking style questionnaire, tests, and interview guidelines. The results showed that concrete sequential subjects tended to write the completion stages sequentially and analyzed them well. Abstract sequential subjects were inclined to solve the problems based on the known concepts without completing the work. Concrete random subjects tended to write information in their own way without completing their work. Meanwhile, abstract random subjects were inclined to write incomplete information and did not complete their work. Generally, based on the IDEALS model, the two sequential subjects were similar in the identity, define, and enumerate steps, while the two random subjects only had similarities in the identity step. This study results imply that jumping tasks can be used as an alternative in developing students critical thinking skills.